Distributed Morphology Today : Morphemes for Morris Halle - Halle, Morris; Marantz, Alec; Matushansky, Ora (Book collections on Project MUSE., 2013)
This book offers a snapshot of current research in distributed morphology, highlighting the lasting influence of Morris Halle, a pioneer in generative linguistics. Distributed morphology, which integrates the morphological with the syntactic, originated in Halle's work. This book, written to mark his 90th birthday, makes an original theoretical contribution to the field and emphasises Halle's foundational contributions to the study of morphology.